PENGEMBANGAN MEDIA SCAFFOLDING STORY DICE (DADU CERITA BERPEMANDU) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS II SD - Hanna Shafira; Moh. Farizqo Irvan (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This research is motivated by the speech block phenomenon observed among second-grade students at SDN Sadeng 03, where students experience cognitive barriers in producing oral language during storytelling. The primary issue focuses on the students' low speaking skills due to the dominance of conventional lecture methods and the lack of interactive media that implement scaffolding strategies. This study aims to develop, test the feasibility of, and prove the effectiveness of Scaffolding Story Dice media in improving speaking skills. The research method employed is Research and Development (R&D) using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of 28 second-grade students at SDN Sadeng 03 for the 2025/2026 academic year. The results showed that the Scaffolding Story Dice media obtained an average feasibility percentage of 94% from media and material experts, categorizing it as "Highly Feasible." Based on field testing, there was a significant difference in speaking ability (p < 0.05), with an increase in the mean score from 54.64 in the pre-test to 82.85 in the post-test. The effectiveness analysis showed an average N-Gain Score of 0.63, which falls into the "Moderate" category. This study concludes that Scaffolding Story Dice media is proven effective in overcoming students communication deadlocks through the integration of visual stimuli and linguistic scaffolding, making it a practical and innovative solution for literacy learning in elementary schools.